Vapor compression refrigeration cycle system modelling and optimization - Lu, Yuanyuan (Nanyang Technological University, 2022)
This work aims to utilize neural networks to depict the high nonlinear system of vapor compression refrigeration cycle (VCRC). The optimization solution has been proposed for the VCRC model.